Perancangan Alat Roll Press Untuk Pembuatan Emping Jagung Kapasitas 150 Kg/Jam Menggunakan Software Solidworks - Pell, Yeremias M.; Odjan, Benediktus Sori; Bunganaen, Wenseslaus (LONTAR Jurnal Teknik Mesin Undana (LJTMU ), 2022)
The development of machine technology that makes it easier for humans to do things more easily and quickly, encourages the world of small and medium-sized corn chip craftsmen to develop home businesses that produce corn chips using a corn chipping machine. The production process with the help of machines can accelerate human performance in carrying out activities. In this design, we will redesign the corn chip machine which already uses a motor to drive a flattened roll that can be adjusted for slack. In this design, the mechanical system of the corn chips roll press machine, the source of rotation is the motor gear that drives the belt and pulley which is connected directly to the reducer which then moves the flattened roll with a chain and sprocket as an introduction. By utilizing the rotation of the gear motor, it can move the flattening roll which will later function to take corn kernels from the inlet funnel. The constant rotation of the motor that drives the flattening roll can work to take corn kernels continuously, thus providing convenience in the process of flattening corn seeds